Summer and nonsummer climatic signals in speleothem δ 18 O revealed by loess microcodium δ 18 O in East Asia - Zeke Zhang; Zhengyu Liu; Gaojun Li; Yanjun Cai; Qin Wen; Hai Cheng; R. Lawrence Edwards; Jing Lei; Heng Liu; Zhaowei Jing; Tao Li; Steven C. Clemens; et al. (Proceedings of the National Academy of Sciences, 2025)
Speleothem δ 18 O records from central southern China have long been regarded as a key benchmark for Asian summer monsoon intensity. However, the similar δ 18 O minima observed among precession minima and their link to seasonal precipitation mixing remains unclear. Here, we present a 400,000-y record of summer precipitation δ 18 O from loess microcodium, which captures distinct precession cycles similar to those seen in speleothem δ 18 O records, particularly during glacial periods. Notably, our microcodium δ 18 O record reveals very low-δ 18 O values during precession minima at peak interglacials, a feature absent in speleothem δ 18 O records from central southern China. This discrepancy suggests that the mixed summer and nonsummer climatic signals substantially influence the speleothem δ 18 O records from central southern China. Proxy-model comparisons indicate that the lack of very low-δ 18 O values in speleothem δ 18 O records is due to an attenuated summer signal contribution, resulting from a lower summer-to-annual precipitation ratio in southern China at strong monsoon intervals. Our findings offer a potential explanation for the long-standing puzzle of the absence of 100- and 41-kyr cycles in speleothem δ 18 O records and underscore the critical role of seasonality in interpreting paleoclimatic proxies in central southern China. These insights also have broader implications for interpreting speleothem δ 18 O records globally, advocating for a more multiseason interpretive framework.